Histomorphochemical comparison of microfracture as a first‐line and a salvage procedure: Is microfracture still a viable option for knee cartilage repair in a salvage situation?. Issue 6 (21st February 2014) - Truong, Minh‐Dung; Chung, Jun Young; Kim, Young Jick; Jin, Long Hao; Kim, Byoung Ju; Choi, Byung Hyune; Min, Byoung‐Hyun
ABSTRACT Microfracture is considered as the first‐line procedure for knee cartilage repair, but the results of microfracture seem less predictable and rather controversial in a salvage situation. Thus, the purpose of the study was to histomorphochemically compare microfracture as a salvage procedure with microfracture as a first‐line procedure in a rabbit model. We hypothesized that microfracture in a salvage situation would result in histomorphochemically inferior cartilage repair compared to microfracture as a first‐line procedure, and the inferiority would be attributed to less migration of reparable marrow cells to the defect due to destruction of microarchitecture of the subchondral bone. Thirty‐six New Zealand white rabbits were divided into three groups: (i) untreated full‐thickness chondral defect, (ii) single microfracture treatment (first microfracture group), and (iii) repeated microfracture in 8 weeks after the first procedure (second microfracture group). In each group, rabbits were sacrificed at the end of 8 weeks, and osteochondral specimens at the repair sites were obtained for histomorphochemical analysis. Results showed that microfracture as a salvage procedure resulted in overall inferior cartilage repair histomorphochemically compared with microfracture as a first‐line procedure, which correlated with deteriorative changes in the quality of underlying subchondral bone rather than intrinsic incapability to recruit the reparative cells in the defect area. In conclusion, although a comparable number of reparable cells and a mechanically weakened subchondral bone are anticipated, more study is necessary to clearly determine when a microfracture should be performed in a situation. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:802–810, 2014.